Bernstein inequality under averaging of elliptic systems in periodic random media - Bondarev, B. V.; Korolev, M. E. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We construct the exponential Bernstein inequality for normed fluctuations of a solution of the Dirichlet problem with rapidly oscillating periodic random coefficients with respect to a solution of the averaged Dirichlet problem.